Efficacy of sutureless and glue free limbal conjunctival autograft for primary pterygium surgery - Malik, K P S; Goel, R; Gupta, A; Gupta, S K; Kamal, S; Malik, V K; Singh, S (Nepalese Journal of Ophthalmology, 2012)
Introduction: There are numerous adjunctive measures described to reduce the recurrence rates after pterygium excision. Objective: To study the efficacy and complications of sutureless and glue free limbal conjunctival autograft for the management of primary pterygium over a period of one year. Materials and methods: A prospective interventional case series was carried out in 40 consecutive eyes with primary nasal pterygium requiring surgical excision. Pterygium excision with limbal conjunctival autografting without using glue or sutures was performed in all the patients followed by bandaging for 48 hours. The patients were followed up post operatively on 2nd day, 1 week, 6 weeks, 6 months and 12 months. They were examined for haemorrhage, wound gape, graft shrinkage, chemosis, graft dehiscence, recurrence or any other complication. Results: The mean age of the patients was 42.8 years (range 23-61), 75% of which were males. Total graft dehiscence occurred in 2 eyes (5%), graft retraction in 3 eyes (7.5%) and recurrence was seen in 1 eye (2.5%). At 6 weeks postoperatively, the gain in uncorrected visual acuity ranged from 0.18 to 0.5 log MAR in 7 eyes. No other complication was noted. Conclusions: Sutureless and glue free limbal conjunctival autografting following pterygium excision is a safe, effective and economical option for the management of primary pterygium. DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6537 Nepal J Ophthalmol 2012; 4 (2): 230-235